Public survey on new in-flight food delivery and waste collection system - Ishak, Farah Diana; Romli, Fairuz Izzudin; Abdul Rahman, Kawthar (Universiti Teknologi MARA, 2018)
The market competition in commercial air transportation industry today is very intense and many airlines are forced to search for new ways to attract potential passengers to their offered flight services. A few studies have shown that service quality is one of the key factors that influence passengers' loyalty to an airline. This includes particularly the in-flight services, which are the main opportunities for airlines to make good impression to their passengers with regards to their overall service. The in-flight food delivery and waste collection process is the primary interest of this study. It is believed that the current manual process of delivering food to passengers and collecting waste afterwards can be significantly improved by automating the process. A public survey is conducted at two major international airports in Malaysia to obtain feedback from the passengers regarding the current and proposed automated food delivery and waste collection processes. Overall, it can be taken that the public has responded positively to the idea. In addition, some characteristics of the proposed process are also established from the survey results, which can be applied when designing and developing the new system.